2017
DOI: 10.1542/peds.2016-2210
|View full text |Cite
|
Sign up to set email alerts
|

A New Case of Congenital Malabsorptive Diarrhea and Diabetes Secondary to Mutant Neurogenin-3

Abstract: Congenital diarrheal disorders are a group of rare enteropathies that often present with life-threatening diarrhea in the first weeks of life. Enteric anendocrinosis, characterized by a lack of intestinal enteroendocrine cells due to recessively inherited mutations in the () gene, has been described as a cause of congenital malabsorptive diarrhea. Diabetes mellitus also is typically associated with mutations, be it early onset or a later presentation. Here we report a case of a 16-year-old male patient with se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 14 publications
0
10
0
1
Order By: Relevance
“…Mutations identified by WES were: a homozygous MALT1 mutation in two siblings with decreased number of Tregs, 34 a homozygous LRBA mutation in two other siblings, 37 a de novo gain-of-function mutation of STAT3 in one girl, and a homozygous MYO5B mutation in one boy in whom marked intestinal inflammation had erroneously led to ascribe the severe diarrhoea to an immune-mediated process. Mutations identified by TNGS included FOXP3 mutations in four boys, for three of whom only DNA was available and in one case normal number and phenotype of regulatory T cells but with abnormal suppressive function; a homozygous NEUROG3 mutation in one boy with chronic diarrhoea since the first months of life and type 1 diabetes since the age of one 38 ; compound heterozygous LRBA mutations in three patients, one boy with two missense mutation, and two siblings with one missense mutation and a large deletion [from exon 3 to exon 48]. As indicated above, this large deletion in LRBA had been missed by WES performed before TNGS.…”
Section: Resultsmentioning
confidence: 99%
“…Mutations identified by WES were: a homozygous MALT1 mutation in two siblings with decreased number of Tregs, 34 a homozygous LRBA mutation in two other siblings, 37 a de novo gain-of-function mutation of STAT3 in one girl, and a homozygous MYO5B mutation in one boy in whom marked intestinal inflammation had erroneously led to ascribe the severe diarrhoea to an immune-mediated process. Mutations identified by TNGS included FOXP3 mutations in four boys, for three of whom only DNA was available and in one case normal number and phenotype of regulatory T cells but with abnormal suppressive function; a homozygous NEUROG3 mutation in one boy with chronic diarrhoea since the first months of life and type 1 diabetes since the age of one 38 ; compound heterozygous LRBA mutations in three patients, one boy with two missense mutation, and two siblings with one missense mutation and a large deletion [from exon 3 to exon 48]. As indicated above, this large deletion in LRBA had been missed by WES performed before TNGS.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have established that neurogenin 3 (Ngn3) is a key transcription factor for EEC differentiation 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36. Consistent with the role of Ngn3 in EEC fate, overexpression of NGN3 in multiple systems has been shown to increase EEC numbers 37, 38.…”
mentioning
confidence: 80%
“…Despite these observations, it remains unclear whether NEUROG3 is absolutely required for beta cell development in humans. In contrast to mouse studies, all reported patients with biallelic mutations in NEUROG3 have functional endocrine cells capable of releasing C-peptide despite severe enteric anendocrinosis from childhood [ 13 ]. All of these cases indicate the presence of insulin-secreting cells, and the reason for this is still elusive.…”
Section: Biological Properties Of Pdx1 Neurog3 and Mafamentioning
confidence: 99%